2011
DOI: 10.5586/asbp.2004.037
|View full text |Cite
|
Sign up to set email alerts
|

SEM and stereoscope microscope observations on the seeds of the Polish species of the genus Sorbus L. (Rosaceae)

Abstract: This paper presents the results of the study on seed morphology of five Polish species of the genus Sorbus L. (S. aria (L.) Crantz, S. aucuparia L. Emend. Hedl., S. chamaemespilus (L.) Crantz, S. intermedia (Ehrh.) Pers. and S. torminalis (L.) Crantz). Observations and measurements were carried out with stereoscope and scanning microscopes. Four types of seed microsculpture were distinguished on the ground of SEM observations. The key to determine Polish species, based on morphological characters of seeds is g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 2 publications
0
16
0
Order By: Relevance
“…The shape and size of cypsela together with other micromorphological features are important revealing characters in species classification. These features can be used at different taxonomic positions to illustrate resemblance among species (Maciejewska‐Rutkowska & Bednorz, ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The shape and size of cypsela together with other micromorphological features are important revealing characters in species classification. These features can be used at different taxonomic positions to illustrate resemblance among species (Maciejewska‐Rutkowska & Bednorz, ).…”
Section: Resultsmentioning
confidence: 99%
“…These features can be used at different taxonomic positions to illustrate resemblance among species (Maciejewska-Rutkowska & Bednorz, 2004).…”
Section: Disparities In Quantitative Charactersmentioning
confidence: 99%
“…In eastern Europe, one of the largest concentrations of S. torminalis occurs in woodlands of the class Querco-Fagetea. In Poland, Slovakia and the Czech Republic, it forms the rare thermophilous association of Sorbo torminalis-Quercetum on acidic soils and is also present in the open, species rich, slightly acidic oak forest Luzulo luzuloidis-Quercetum genistetosum tinctoriae of Poland (Kwiatkowski 2003: Bednorz 2007bMad era et al 2012;Szymura 2012). In Slovakia, S. torminalis is also a component of the basic soil version of the dry-mesic woodland Corno-Quercetum (Prudi c 1998;Role cek 2005).…”
Section: Communitiesmentioning
confidence: 99%
“…In contrast, Rasmussen & Kollmann (2007) found that fencing to exclude roe deer (Capreolus capreolus L.) resulted in root suckers growing a mean of 3Á8 cm in height in one season compared to 0Á6 cm outside exclosures. Certainly, a number of authors suggest that browsing is usually severe enough to prevent the natural regeneration of S. torminalis (Bednorz 2009;Bednorz, Ka zmierczak & Kaczmarek 2012;Mad era et al 2012).…”
Section: Response To Biotic Factorsmentioning
confidence: 99%
“…It is known that fruit and seeds are very useful in identification and classification of plant taxa (Karcz 1996;Liu and Lin 1999;Özcan 2004;Maciejewska-Rutkowska and Bednarz 2004;Fagúndez and Izco 2004). Description of achenes from taxa of P. collina group is limited to their length, shape and colour (Wolf 1908;Juzepczuk 1941;Kelley 1953;Szafer and Paw³owski 1955;Soják 1995).…”
Section: Introductionmentioning
confidence: 99%